Identification and validation of CKAP2 as a novel biomarker in the development and progression of rheumatoid arthritis - Zheng, Qiongbing; Lan, Youmian; Chen, Jiexin; Lin, Ling (Frontiers in Immunology, 2025)
BackgroundRheumatoid arthritis (RA) is a common chronic joint disease. However, many patients exhibit inadequate responses to treatment due to disease heterogeneity. Identifying novel biomarkers for RA is crucial for advancing molecular diagnosis and identifying potential therapeutic targets.MethodsSynovial tissue transcriptome data from RA patients and healthy controls were obtained from the GEO database. Differentially expressed gene (DEG) analysis, functional enrichment analysis, and weighted gene co-expression network analysis (WGCNA) identified key gene modules in RA. Machine learning algorithms were used to identify hub genes, followed by immune infiltration analysis and gene set variation analysis (GSVA). Mendelian randomization (MR) analysis explored the causal relationship between hub genes and RA. Clinical synovial tissue samples were used to validate CKAP2 expression via quantitative real-time polymerase chain reaction (qRT-PCR), western blot, and immunohistochemistry (IHC). The potential role of CKAP2 in the pathogenesis of RA was investigated through CCK-8 assay, wound healing assay, transwell migration assay and transwell invasion assay.ResultsA total of 242 DEGs were identified between 20 RA patients and 17 healthy controls. Six gene modules were recognized, with the “turquoise” module associated with RA (cor = 0.39, p = 0.00017). Three hub genes, CKAP2 (AUC = 0.876), POU2AF1 (AUC = 0.885), and HLA-DOB (AUC = 0.897), involved in the IL-6/JAK/STAT3 signaling pathway and inflammation, were identified. Immune infiltration analysis showed these genes were associated with plasma cells and T cell infiltration. MR analysis confirmed a causal relationship between CKAP2 and RA. qRT-PCR, western blot, and IHC demonstrated CKAP2 expression was higher in RA synovial tissue compared to osteoarthritis (OA) samples. Cellular functional assays demonstrated that CKAP2 knockdown inhibited the proliferation, migration, and invasion of MH7A and HFLS-RA cells.ConclusionCKAP2, a signature gene in RA, is highly expressed in RA synovial tissues, and contributes to the pathogenesis of RA by promoting the proliferation, migration, and invasion of MH7A and HFLS-RA cells. This gene holds potential as a novel biomarker for RA and provides valuable insights into its molecular diagnosis and targeted therapies.